Diagnostic lncRNA high expression for liver patients prognosis and medication guidance: a systematic review and meta-analysis - Zhu, Hengzhou; Chen, Haoyan; Zhu, Xiaodan; Zhang, Baonan; Jin, Chunhui (Frontiers in Pharmacology, 2024)
The study of long non-coding RNAs (lncRNAs) has gained significant attention due to their roles in regulating gene expression and their potential as diagnostic biomarkers. This systematic review and meta-analysis aimed to evaluate the diagnostic value of high-expression lncRNAs in liver disease patients, including those with hepatitis, cirrhosis, and hepatocellular carcinoma (HCC).Methods: A comprehensive literature search was conducted across multiple electronic databases, including PubMed, Embase, Web of Science, and Cochrane Library, up to July 2024. Studies were included if they investigated the expression of lncRNAs in liver disease patients and evaluated their diagnostic performance. The Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool was used to assess the quality of included studies. Pooled sensitivity, specificity, diagnostic odds ratios (DOR), and summary receiver operating characteristic (SROC) curves were calculated using a bivariate random-effects model.Nine studies involving 888 samples were included in the meta-analysis. The pooled hazard ratio (HR) for overall survival (OS) was 2.01 (95% CI: 1.71 to 2.36), indicating a significant association between high lncRNA expression and poor liver disease outcomes. Subgroup analyses revealed a pooled odds ratio (OR) of 1.99 (95% CI: 1.53 to 2.60) for tissue samples and 8.62 (95% CI: 1.16 to 63.71) for blood samples, suggesting a stronger diagnostic value for blood-based lncRNAs. The funnel plots indicated minimal publication bias, and sensitivity analyses confirmed the robustness of the findings.High-expression lncRNAs show significant potential as diagnostic biomarkers for liver diseases, offering non-invasive, accurate, and timely diagnostic information. Despite the promising results, further research is needed to standardize detection methods, elucidate the biological functions of lncRNAs, and validate their clinical utility in diverse patient populations. Integrating lncRNA biomarkers with traditional diagnostic approaches could enhance diagnostic accuracy and improve patient management and outcomes in liver disease.